PENGUKURAN KINERJA PERUSAHAAN DENGAN PENDEKATAN BALANCED SCORECARD (Studi Kasus Pada Kontraktor PT X) - DEWI, RINA (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
ABSTRACTIn the face of the business environment with state of intense competition as the current performance measurement methods are needed to assess the company's performance accurately and comprehensively. Performance measurement tool that combines the size of financial and non financial performance is the Balanced Scorecard, which measures performance from four perspectives, namely financial perspective, customer perspective, internal business perspective, and learning and growth perspective. This study aims to discuss the measurement of the performance of the private sector, namely the contracting company PT X by using the Balanced Scorecard method using data from 2014 and 2015. The method used in this research is descriptive analysis method. Data collection techniques include primary data by conducting interviews, direct observation and secondary data to obtain documentation of the company and literature related to the research topic. Results of research have shown that the application of the balanced scorecard as a performance measurement system at PT. X can describe the results of the company's performance based on the achievement of targets by which have been formulated into each - each of our strategic objectives is a translation of the vision and mission of the company. The results of evaluation of performance measurements based on the balanced scorecard that includes all four perspectives both financial and non-financial was able to pose a strategic plan can be formulated, defined and achievable in the future in an effort to improve or enhance the performance of the company.Â Keywords: Balanced scorecard, Performance Measurement